“Wandering is your fate”: Esther Shumiatcher-Hirschbein Writing Across Boundaries - Jones, Faith (Canadian Jewish Studies / Études juives canadiennes, 2003)
This essay provides an overview of the life and creative work of Esther Shumiatcher-Hirschbein, Yiddish poet and wife of Yiddish playwright Peretz Hirschbein. Shumiatcher-Hirschbein was a Jewish immigrant to Calgary at the turn of the twentieth century, and a member of a family that contributed in various ways to Canadian culture. Shumiatcher-Hirschbein left Canada with her husband, entering into a life of adventure and travel, and coming in contact with bohemian and artistic Yiddish circles around the world. Shumiatcher-Hirschbein’s poetry, its reception by critics, and its relationship to her biography are all examined.